Pengaruh Progressive Muscle Relaxation (PMR) terhadap Penurunan Tekanan Darah pada Lansia Hipertensi di Panti Sosial Tresna Wherda Palembang Provinsi Sumatera Selatan Tahun 2018 - Mareta Akhriansyah (Jurnal Ilmiah Universitas Batanghari Jambi, 2019)
Hypertensioncan we call as “silent killer” because it could be making an ice mountain fenomenal. Hypertension prevalence will increasing with getting older of that people. Identical of Hypertension is a increasing of blood pressure more than normal limit.The aim of this study was to know an influence of relationship between  progresive muscle relaxationtoward decreasing blood pressure of old peoplehypertension in Nursing Home. This study used“Quasi Experimental Pre-Post Test With Control Grup”design withProgresive Muscle Relaxation (PMR) intervension, sample is taking by purposive sampling technique with 30 respondents, which they are divided into 2 group as treatment group and control group. Both of that groups are getting measurement of their blood pressure. The result showed that after Progresive Muscle Relaxation Exercise there is a decreasing systolic of blood pressure 28,7 mmHg and decreasing dyastolic of blood pressure 18 mmHg.And finally this study having conclusion that Progresive Muscle Relaxation Exercise can make decreasing blood pressure systolic and dyastolic with certainly result(p=0.000<α =0.05). To increasing a healthy Old People meassurement there must be a policy development  to make progressive muscle relaxation exercise will application well to Old People Hypertension